Ulcerations on the Hands and Fingers. Issue 4 (July 2017) - Agnetta, Vlatka; Jacob, Sharon E.
Abstract : ABSTRACT: Teledermatology is a term to describe the provision of dermatologic medical services through telecommunication technology. This is a teledermatology case of ulcerations on the hands and fingers.